Modeling mortality risk in patients with severe COVID-19 from Mexico - Cortes-Telles, Arturo; Figueroa-Hurtado, Esperanza; Ortiz-Farias, Diana Lizbeth; Zavorsky, Gerald Stanley (Frontiers in Medicine, 2023)
Background: Severe acute respiratory syndrome caused by a coronavirus (SARS-CoV-2) is responsible for the COVID-19 disease pandemic that began in Wuhan, China, in December 2019. Since then, nearly seven million deaths have occurred worldwide due to COVID-19. Mexicans are especially vulnerable to the COVID-19 pandemic as Mexico has nearly the worst observed case-fatality ratio (4.5%). Since Mexican Latinos represent a vulnerable population, this study aimed to determine significant predictors of mortality in Mexicans with COVID-19 who were admitted to a large acute care hospital. Methods: In this observational, cross-sectional study 247 adult patients consecutively admitted to a third-level referral centre in Yucatan, Mexico, from March 1st, 2020, to August 31st, 2020 with COVID-19-related symptoms, participated in this study. Lasso logistic and binary logistic regression were used to identify clinical predictors of death. Results: After a hospital stay of about eight days, 146 (60%) patients were discharged; however, 40% died by the twelfth day (on average) after hospital admission. Out of 22 possible predictors, five crucial predictors of mortality outcome were found, ranked by the most to least important: (1) needing to be placed on a mechanical ventilator, (2) platelet concentration at admission, (3) derived neutrophil to lymphocyte ratio at admission, (4) age, and (5) pulse oximetry saturation at admission. Increases in platelet concentration and pulse oximetry and decreased number of days of hospital stay decreased the likelihood of mortality. Due to multicollinearity, the number of days of hospital stay was removed, and the final model is presented with the other five significant predictors. Conclusions: Of the 247 Mexican Latinos patients admitted with COVID-19, 40% died 12 days after admission. The patients’ need for mechanical ventilation (due to severe illness) was the most important predictor of mortality, as it increased the odds of death by nearly 200-fold.